Correlation between serum uric acid levels and outcomes of pre-eclampsia in Abakaliki, South-east, Nigeria - Adiele, Nnabugwu A.; Umeora, Odidika U. J.; Onoh, Robinson C.; Dimejesi, Ikechukwu B. O.; Ikeotuonye, Arinze C.; Adiele, Nkemjika M.; Olaleye, Ayodele A.; Nwafor, Amuchechukwu V. (International Journal of Research in Medical Sciences, 2021)
Background: Pre-eclampsia is a leading cause of fetomaternal and perinatal morbidity and mortality. The role of serum uric acid (SUA) in determining the complications of preeclampsia has been controversial. This study compared mean SUA levels between severe pre-eclamptics and normotensive women at term and ascertained its correlation with outcomes of preeclampsia; as well as determined if there is a threshold value of SUA level beyond which fetomaternal complications occur. Methods: A case-controlled study where 80 severe pre-eclamptics at term and 80 normotensive women matched for gestational age were recruited. Blood samples were collected from them for assay of SUA levels and they were followed till delivery. The fetomaternal outcomes and the corresponding SUA levels at diagnosis were documented and variables statistically analyzed. A receiver operating characteristic curve was used to determine the cut-off value of SUA beyond which adverse fetomateral complications are likely to occur in pre-eclampsia. Results: The mean SUA level in severe pre-eclamptics (0.283±0.09 mmol/l) was not significantly higher than that of normotensive women (0.263±0.09 mmol/l, p=0.13). There was a weak positive correlation between the SUA levels and fetomaternal outcomes [maternal (r=0.102, p=0.236) and fetal (r=0.096, p=0.226)]. The study was unable to identify the threshold SUA level at which adverse fetomaternal outcomes occur as the values of SUA were closely related. Conclusions: SUA levels of pre-eclamptics and normotensive women did not show significant difference and correlated weakly with fetomaternal outcomes and are therefore poor predictor of fetomaternal outcomes in pre-eclampsia.